1990
DOI: 10.1515/rnam.1990.5.4-5.359
|View full text |Cite
|
Sign up to set email alerts
|

Variational difference method for elliptic problems with highly quasi-singular quadratic forms

Abstract: The paper considers the problem of construction of the best approximate solution (using the variational difference method) to two model elliptic boundary value problems with essentially different types of high quasi-singularity of the corresponding quadratic form.To solve approximately elliptic problems [9] by the variational difference method, sufficient conditions for localization of singularities and quasi-singularities [7] of these problems were obtained in [4,5,6]. The original domain was assumed to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In this paper we continue to study the model problems [1][2][3][4][5][6][7]. The method of dividing the arbitrary original problem (with certain properties) into subproblems that are reduced to the model problems has adequately been studied by the author in [1][2][3][4].…”
Section: Posing the Problemmentioning
confidence: 99%
“…In this paper we continue to study the model problems [1][2][3][4][5][6][7]. The method of dividing the arbitrary original problem (with certain properties) into subproblems that are reduced to the model problems has adequately been studied by the author in [1][2][3][4].…”
Section: Posing the Problemmentioning
confidence: 99%
“…The universal constants are numerated within every section. Note that in [1,[3][4][5][6][7][11][12][13] it has been shown, in fact, that the variation-difference method is optimal for solving a wide class of both regular and irregular problems & f ( in the traditional formulation) and Sy. Special condensing grids, and, sometimes, special finite elements constructed on the basis of the predetermined differential properties of solutions of these problems have been used therein for solving irregular classes of the problems.…”
Section: Posing the Problemmentioning
confidence: 99%
“…Javadian [7] constructed an optimal method (a variation-difference one) for solving this problem (see Definition 1.1). He also showed that the following relation held for sufficiently large N:…”
Section: A Class Of Problems With Strong Quasi-degeneration Of the Qumentioning
confidence: 99%
“…For all quasisingular classes of elliptic problems (QCEP) studied by the author in [3][4][5][6][7][8] condensed finite element grids were constructed to get an optimal approximate solution in the sense of (d N N)-width of Kolmogorov. It means that we chose N from the relation d N H. Then using a priori differential properties of QCEP under investigation, we constructed a certain condensed N-nodal finite element grid to get an accuracy H in energy norm.…”
Section: Introductionmentioning
confidence: 99%